Broad Realization Data Processing Applications Agricultural Intensification Program Crops at the Lampung Regency Agriculture Office North - Desmi Ulfa; Riska Wati (Institut Bakti Nusantara, 2020)
The Agriculture Office of North Lampung Regency is one of the beneficiaries of the Agricultural Intensification Program from the Directorate General of Food Crops with the distribution of assistance through 23 District Technical Implementation Units (UPTD) of North Lampung District. All UPTD Sub-districts receiving assistance from the Agricultural Intensification Program should make a report of the actual crops realized from the program. In processing the report data is the Agriculture Office of North Lampung Regency still using Microsoft Excel application. Therefore, the researcher tries to make a special application to input the data of broad realization of agricultural intensification program programs using Prototype method with Borland Delphi 7.0 program. This application is expected to facilitate officers in inputting data such as commodity data, UPTD data, realization data and officer data.